DIALEK MELAYU PAPUA: SUATU SEJARAH SINGKAT - Suharyanto NFN (Balai Bahasa Provinsi Papua, 2019)
This paper discusses about Papuan Malay Dialect, one of the variant of Malay language used in Papua. It aims to recognize the origin of this dialect, when it is started to use and about its spread around. Method which is used in this paper is literature review and the result shows us that this dialect is a variant of Malay language which comes from West Kalimantan. This variant spread out in Papua region about VII century A.D. It is spread out by three mutually complement courses, namely, missionary, trade, and political courses. Missionary course occurs when Islam and Christian started to be spread out in Papua. Trade course occurs through trading contact between Malay speaker and Papuan indigenous people. And then political course occurs through political contact between authority in Papua and another one, either in Nusantara (Indonesia) or abroad.